Separate pathways to violent behavior in schizophrenia and in the general population. (July 2022) - Krakowski, Menahem I.; Tural, Umit; Czobor, Pal
Abstract: Violence in schizophrenia is best investigated within the broader context of violent behavior in the general population. Two important domains of general pathology which allow us to take such an approach include impairment in emotion processing, as manifested by faulty facial emotion recognition, and aggressive reactivity which consists of heightened sensitivity to provocation. To test this approach, we included 135 subjects: 38 violent (VS's) and 33 nonviolent patients with schizophrenia, 32 healthy controls and 32 non-psychotic violent subjects (NPV's). We measured violence with the Life History of Aggression Scale, recognition of facial emotions with the Emotion Recognition Task, and aggressive reactivity through the Buss-Perry Aggression Questionnaire. Adolescent antisocial behavior was evaluated as a potential precursor to these deficits. We found that impairment in fear recognition (IFR) and aggressive reactivity have a significant effect on violence in the violent groups. These two impairments interact in different ways in these groups. In NPV's they contribute in an additive fashion to violence, whereas in VS's they represent separate pathways; aggressive reactivity leads to violence only when there is no IFR. Adolescent antisocial behavior has a differential effect on these 2 impairments in the 2 groups. Thus, these findings provide insights on the differential role of IFR and aggressive reactivity for violence in schizophrenia compared to the general population. In NPV's, both dysfunctions represent antisocial features and contribute jointly to violence. In schizophrenia, they have different etiologies and constitute alternative pathways to violence. This has important implications for the conceptualization and treatment of violence. Graphical abstract: Image 1 Highlights: Violence in schizophrenia studied in the context of violence in general population. Violent patients with schizophrenia and non-psychotic violent subjects are compared. Fear recognition impairment and aggressive reactivity lead to violence in both groups. In non-psychotic subjects these two impairments contribute additively to violence. In schizophrenia these impairments constitute separate pathways to violence.